2015
DOI: 10.1063/pt.3.3020
|View full text |Cite
|
Sign up to set email alerts
|

Diatomic molecules, a window onto fundamental physics

Abstract: Electronic structure enhancement factors of simultaneous parity and time-reversal violation (P, Tviolation) caused by an electric dipole moment of the electron (eEDM) and scalar-pseudoscalar nucleon-electron current (SPNEC) interactions are reported for various metal mono-hydroxides, several of which are considered laser-coolable and promising candidates for an eEDM measurement. Electronic structure enhancements are calculated ab initio within zeroth order regular approximation (ZORA) for CaOH, SrOH, BaOH, RaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 61 publications
1
41
1
Order By: Relevance
“…It appeared from the early work of Sandars in 1964 [9] that molecules with large electric polarization have larger effective electric fields. This idea is now commonly accepted [10][11][12]. However, recently, we reported that YbH and HgH have larger Eeff than YbF and HgF, although their polarizations are smaller [13].…”
Section: Introductionmentioning
confidence: 90%
“…It appeared from the early work of Sandars in 1964 [9] that molecules with large electric polarization have larger effective electric fields. This idea is now commonly accepted [10][11][12]. However, recently, we reported that YbH and HgH have larger Eeff than YbF and HgF, although their polarizations are smaller [13].…”
Section: Introductionmentioning
confidence: 90%
“…It is a commonly held idea that as the molecules become more polarizable their E eff becomes larger. This is even mentioned in a recent article in Physics Today [12].…”
Section: Introductionmentioning
confidence: 94%
“…In practice, the perpendicular component is obtained by placing the internuclear axis on either the x-or y-axis while the quantization axis of total electronic angular momentum is kept along the z-axis, effectively using the expression in Eq. (15). A similar scheme was recently presented in the framework of the complex generalized Hartree-Fock and Kohn-Sham methods.…”
Section: Theorymentioning
confidence: 99%